The social and political life of names and naming - Reuben Rose-Redwood (Nordisk Tidskrift för Socioonomastik)
This concluding commentary critically and constructively engages with the articles in this first multidisciplinary issue of the Nordic Journal of Socio-Onomastics. It does so in the spirit of affirmative critique, with the aim of advancing the ongoing dialogue on the social and political life of names and naming. The commentary concludes by arguing that the multidisciplinary field of socio-onomastics is best viewed as a contact zone, or space of convergence, for scholarship that examines the diverse ways in which names and naming shape, and are shaped by, worlds-in-the-making.